SINTESIS ASETIL ASKORBAT MELALUI ASETILASI TANPA PELARUT DAN KATALIS - Nurhidayah, Annisa; Daniel, Daniel; Hiyahara, Irfan Ashari (JURNAL ATOMIK, 2021)
ABSTRACT The preparation of acetyl ascorbate by acetylation without solvent and catalyst has been carried out. The preparation of acetyl ascorbate is carried out by reacting ascorbic acid with anhydrous acetic acid using a 1:1 mole ratio without solvent and catalyst. The acetylation reaction was carried out using the reflux method at 700C for 5 hours. The result of acetyl ascorbate acetylation is a yellow powder with a yield percentage of 71.8182%. The functional groups of the synthesized compound in the form of acetyl ascorbate were analyzed using a FT-IR spectrophotometer. The FT-IR analysis results show the functional groups OH, CH sp3, C=C, C=O ester and C-O-C ester. Based on these results it can be seen that acetyl ascorbate has been formed.